A call for collaboration: Perception of religious and spiritual leaders on mental health (A Portuguese sample). Issue 1 (2nd January 2019) - Freire, Jaclin; Moleiro, Carla; Rosmarin, David H.; Freire, Marina
ABSTRACT: To assess the relationship and collaborations between mental health professionals and religious and spiritual leaders, eleven representatives of ten different religious affiliations in Portugal participated in this qualitative study. Major findings reported showed that religious leaders perceive themselves as important agents in promoting and preserving their congregants' mental health, as well as aiding their recovery processes; however this occurs without much referral to or collaboration with mental health professionals. These findings are discussed, as well as why and how a healthy collaboration between mental health professionals and religious leaders can positively impact the psychotherapeutic relationship and clinical outcomes with religious/spiritual clients.